42nd IEEE International Conference on Decision and Control (IEEE Cat. No.03CH37475)
DOI: 10.1109/cdc.2003.1272630
|View full text |Cite
|
Sign up to set email alerts
|

Controllability and optimization for differential linear repetitive processes

Abstract: Differential linear repetitive processes are a class of continuous-discrete 2D systems of both systems theoretic and applications interest. The feature which makes them distinct from other classes of such systems is the fact that information propagation in one of the two independent directions only occurs over a finite interval. In this paper we develop an operator theory approach for the study of basic systems theoretic structural and control properties of these processes. In particular, we first develop a ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…We denote by U T ⋅ ( ) the set of the all T-admissible control functions for the system (1) -(3) corresponding to the set  in (7). By analogy with [9; 10] it can be shown that  is the convex set.…”
Section: T H -[ ]mentioning
confidence: 99%
See 1 more Smart Citation
“…We denote by U T ⋅ ( ) the set of the all T-admissible control functions for the system (1) -(3) corresponding to the set  in (7). By analogy with [9; 10] it can be shown that  is the convex set.…”
Section: T H -[ ]mentioning
confidence: 99%
“…Moreover, it is already known that [6] links between some types of linear repetitive processes and delay systems, which can, where appropriate, be used to great effect in the control related analysis of these processes. This paper is based on the work [7] and gives some new results on optimisation theory for delayed differential-difference linear processes. There are only a few research works in the literature devoted to optimisation theory (see, for example [8], and references therein).…”
Section: Introductionmentioning
confidence: 99%